Analisis Efisiensi Biaya dan Profitabilitas Usaha Pembibitan Tanaman Di CV. Perapi Kecamatan Kambu Kota Kendari - Rusman, Rusman; Iswandi, R. Marsuki; Salam, Idrus (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
Plant nursery business is one of the businesses that have the ability to produce high profits, in the cultivation of plant seeds consisting of coconut, patchouli, nutmeg, cashew, teak, Jabon, biti, and mahogany. The availability of raw materials, consumer demand, and seed prices is a major factor in the sustainability of the nursery business. The purpose of this study was to determine the cost efficiency and profitability of plant nursery businesses in the CV. Perapi Kambu District Kendari City. The research location was determined purposively with the consideration that the plant nursery company was one of the largest producers of seedlings in Kendari City. The analytical method used in this research is a descriptive and analytical method. The analysis used is R-C ratio analysis and Return On Investment (ROI). The results showed that the use of production costs in one production in a plant nursery was classified as efficient, as indicated by the ratio of R-C 1.96 (R-C ratio> 1) and based on Return On Investment analysis with a value of 69% indicating that the nursery business was profitable.